Level of knowledge and compliance with the vaccination scheme in mothers of children under 2 years of age who attend the public health center of the Province of Huancayo 2019 - Gutierrez Mancha, Yeni Mayvel (2020)
Objectives: To determine the level of knowledge and compliance with the vaccination scheme in mothers of children under 2 years of age who attend the public health center of the Province of Huancayo 2019. Material and Methods: Being the study variables level of knowledge and compliance with the vaccination scheme. The study method was descriptive of cross section, the sample consisted of 123 mothers of children under 2 years. Results: 123 (100%) mothers surveyed of children under 2 years of age who attended the public health center of the Province of Huancayo from January to June 2019. 108 (87.38%) mothers have a high level of knowledge about the vaccination scheme and 123 (100%) revised vaccination cards of mothers of children under 2 years of age,103 (83.7%) comply with the vaccination scheme and 20 (16.3%) do not comply with the vaccination scheme. Conclusions: Of 123 (100%) mothers surveyed of children under 2 years of age who attended a public health center in the Province of Huancayo according to the high level of knowledge 93 (86.1%) comply with the vaccination scheme being adequate.